Nanoscale polarization relaxation and piezoelectric properties of SBN thin films - Melo, M. [UNESP]; Araujo, E. B. [UNESP]; Ivanov, M.; Shur, V. Y.; Kholkin, A. L. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
Randomly oriented Sr0.75Ba0.25Nb2O6 thin films have been deposited on Pt(111)/Ti/SiO2/Si substrates using a polymeric chemical route to study their peculiar nanopolar structures and local ferroelectric properties using piezoresponse force microscopy (PFM) technique. PFM images reveals grains with contrast among fully white and fully black, a clear indication of non-zero polarization in the SBN films far above Tm ∼ 221 K. Asymmetries observed in local hysteresis loops recorded at different grains suggest an imprint effect in the studied films due to an internal build-in electric field. Some grains show asymmetric hysteresis loops while other grains show symmetric hysteresis loops. The origin of the imprint effect observed in the SBN films is discussed in terms of complex defects associated to oxygen vacancies. The experimental relaxation curves were fitted using the Kohlrausch-Williams-Watts function. The time constant τ increases from 404 to 977 ms as the magnitude voltage increases.
Keywords: piezoresponse; polarization relaxation; SBN films